Material with complete magnetic compensation effect and high longitudinal spin polarization and preparation method and application thereof
By designing semi-metal fully compensated ferromagnetic materials with full magnetic compensation effect, the limitations of existing semi-metal materials in achieving 100% spin polarization current are solved, and longitudinal current with high spin polarization rates and a wide range of spin electronics applications are achieved.
Patent Information
- Application Number
- CN202510363814.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-06-27
AI Technical Summary
The existing semi-metallic materials have limitations in achieving 100% spin polarization current, and semi-metallic materials with other magnetic characteristics have not been fully developed and are difficult to meet the needs of different applications.
By designing a semi-metal fully compensated ferromagnetic material with a complete magnetic compensation effect, the chemical formula is Mn2-aVaFe1-bXbGa1-cYc, the longitudinal current with high spin polarization can be achieved through the adjustment of temperature and composition, and the longitudinal electric transport characteristics, abnormal Hall parameters and magnetic compensation parameters can be optimized and continuously adjusted.
It achieves the generation of 100% spin polarization current in a zero-field environment, extends the spin polarization transmission distance to 1 cm, and provides a wide range of application prospects for spin electronic devices.
Smart Images

Figure CN120210632A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a half-metal fully compensated ferrimagnetic material, and particularly to a material with a fully compensated effect of high spin polarization, a preparation method thereof, and an application thereof. Background Art
[0002] Spin electronic data storage devices such as giant magnetoresistance (GMR) and tunneling magnetoresistance (TMR) are important tools for quantum information processing and probabilistic computing. In spin electronic materials, in addition to controlling the electron charge, it is also necessary to control the electron spin. In particular, a 100% spin-polarized current source is very suitable for application in advanced spin electronic devices. Materials that can achieve 100% spin polarization can be realized using half-metals, and half-metals exhibit metallic behavior in one spin direction and insulating or semiconductor behavior in the other direction. However, such half-metals need to be designed by atomic-level engineering, and so far, only a few half-metals have been developed, such as Heusler alloys, CrO2, NiMnSb, etc.
[0003] So far, the reported half-metals usually have ferromagnetism. However, half-metals with other magnetic characteristics may lead to the development of new spin electronic devices. One case proposed in 1995 is half-metal fully compensated ferrimagnetism. These are usually referred to as half-metal antiferromagnets; however, antiferromagnets themselves cannot be half-metals because their spin rotation symmetry is incompatible with half-metallicity. Instead, although fully compensated ferrimagnets behave magnetically like antiferromagnets, they can be used as half-metals. A remarkable feature of half-metal fully compensated ferrimagnets is that no static magnetic field is generated inside them; therefore, when the temperature approaches 0K, the total magnetic moment decreases and the magnetostatic energy is low. Therefore, half-metal fully compensated ferrimagnets will contribute to generating 100% spin-polarized current in a zero-field environment, promoting the development of new spin electronic devices different from those prepared by traditional methods. For this purpose, theoretical calculations for identifying half-metal fully compensated ferrimagnetic materials have been carried out for more than 25 years, and many possible half-metal fully compensated ferrimagnetic materials and their properties have been predicted. However, most of them are not practical or only appear in unstable crystal structures. Currently, half-metal fully compensated ferrimagnetism has only been found in Heusler alloys (Mn 1.5 V 0.5 FeAl bulk and Mn2V 0.5 Co 0.5 Al melt-spun ribbons) with an L21-type crystal structure, and (CrFe)S powders with a NiAs-type structure. These half-metal fully compensated ferrimagnets exhibit N-type ferromagnetism as predicted by Néel.
[0004] The practical applications and device designs based on the complete compensation effect often need to meet different requirements, which requires the materials with the complete compensation effect to have continuously tunable physical properties and a rich variety of candidate materials. Summary of the Invention
[0005] Therefore, the purpose of the present invention is to provide a series of half-metallic complete compensation ferrimagnets substituted by different elements, and to optimize and continuously tune the longitudinal electrical transport properties, anomalous Hall parameters, and magnetic compensation parameters of such materials through temperature, composition, etc. To achieve a longitudinal current with a high spin polarization rate. The longitudinal conducting electrons have opposite spin polarization directions on both sides of the sample, and the spin polarization transport distance can reach up to 1 cm.
[0006] The present invention provides a material with a complete magnetic compensation effect and high longitudinal spin polarization, and its chemical formula is: Mn 2-a V a Fe 1-b X b Ga 1-c Y c , where X is selected from one or more of Cu, Ni, Co, Cr, and Ti, Y is selected from one or more of Al, Ge, In, Si, Pb, Sb, and Sn, 0 ≤ a ≤ 1, 0 ≤ b ≤ 1, 0 ≤ c ≤ 1, and 0 < a + b + c < 3; Before doping, Mn2FeGa has a simple cubic structure with the space group Pm-3m (No.221). After doping, the crystal structure is a face-centered cubic structure with the space group F-43m (No.216) or the space group Fm-3m (No.225).
[0007] Preferably, the material is an alloy bulk material; the material has magnetic full-compensation ferrimagnetic properties, that is, the material has a magnetic full-compensation point, and at the magnetic full-compensation point, the material exhibits antiferromagnetism; the full-compensation point of the material is adjusted by the types and compositions of the doping elements;
[0008] The material has high longitudinal spin polarization characteristics in the temperature range of 120 - 400K. The carriers transported longitudinally have opposite spin polarization directions on both sides of the alloy bulk material, and the spin polarization transport distance reaches 1 cm.
[0009] Preferably, it includes the following steps:
[0010] (1) According to the chemical formula Mn 2-a V a Fe 1-b X b Ga 1-c Y cWeigh the raw materials, where X is selected from one or more of Cu, Ni, Co, Cr, and Ti, Y is selected from one or more of Al, Ge, In, Si, Pb, Sb, and Sn, 0 ≤ a ≤ 1, 0 ≤ b ≤ 1, 0 ≤ c ≤ 1, and 0 < a + b + c < 3;
[0011] (2) Use the electric arc furnace melting method to make the raw materials into an alloy material.
[0012] Preferably, in step (1), the weighing of the raw materials specifically includes using Mn, V, Fe, X, Ga, and Y elements with a purity of not less than 99.9%, weighing according to the atomic ratio of the alloy, and the total mass is not less than 5 grams.
[0013] Preferably, to offset the volatilization of Mn element during the melting process, in step (1), the following steps are also included: weighing 5 at.% more of the total number of Mn atoms to balance the melting loss.
[0014] Preferably, the electric arc furnace melting method includes the following steps:
[0015] Place the volatile Mn at the bottom of the vacuum arc furnace crucible and cover it evenly with other materials, then repeatedly introduce high-purity argon into the furnace cavity three times to ensure that the high-temperature state during the melting process will not oxidize the sample;
[0016] During the melting process, the melting time for each side is 4 minutes, and it is turned over back and forth three times in total to ensure uniform melting, and the melting loss is controlled below 1%;
[0017] Put the uniformly melted sample into a quartz tube and vacuum seal it, conduct heat treatment at 800 - 1100 °C for 150 - 200 hours in a box-type muffle furnace, and then quench it in an ice-water mixture;
[0018] After quenching, break the quartz tube to take out the sample, and use a cutting machine and a grinding and polishing machine to perform cutting, grinding, and polishing operations respectively to obtain a regular rectangular block material.
[0019] The present invention also provides the application of the material with complete magnetic compensation effect and high longitudinal spin polarization, which is applied to the preparation of spintronic devices.
[0020] Preferably, the spintronic devices include magnetic sensors, magnetic random access memories, and spin transfer torques.
[0021] The material proposed by the present invention is a half-metal fully compensated ferrimagnet through a series of different element substitutions, and the longitudinal electrical transport characteristics, anomalous Hall parameters, and magnetic compensation parameters of this type of material are optimized and continuously adjustable through temperature, composition, etc. A longitudinal current with a high spin polarization rate is achieved. The longitudinal conduction electrons have opposite spin polarization directions on both sides of the sample, and the spin polarization transmission distance can reach up to 1 cm at most.
[0022] The material provided by the present invention has high longitudinal spin polarization, high spin polarization and complete compensation effect. It is a series of magnetic half-metal Heusler materials substituted by different elements. Through mechanisms such as composition and temperature regulation, the Curie temperature, magnetic compensation temperature, longitudinal electrical transport properties, Hall parameters and other properties of this type of material can be optimized and continuously adjusted, and it has a complete compensation effect. Therefore, this material has broad application prospects in spin electronics devices such as spin polarization injection, magnetic sensors, field effect transistors and magnetic random access memories. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Magnetization intensity-temperature curve of the Mn 1.8 V 0.2 FeGa alloy prepared in Example 1 of the present invention measured under a magnetic field of 2000 Oe;
[0024] Figure 2 Longitudinal resistivity-temperature curve of the Mn 1.8 V 0.2 FeGa alloy prepared in Example 1 of the present invention;
[0025] Figure 3 XRD pattern of the Mn 1.7 V 0.3 FeGa alloy prepared in Example 2 of the present invention;
[0026] Figure 4 Magnetization intensity-temperature curve of the Mn 1.7 V 0.3 FeGa alloy prepared in Example 2 of the present invention measured under a magnetic field of 2000 Oe;
[0027] Figure 5 Hall conductivity-magnetic field curve of the Mn 1.7 V 0.3 FeGa alloy prepared in Example 2 of the present invention;
[0028] Figure 6 Local longitudinal resistivity-magnetic field curve and its test schematic diagram of the Mn 1.7 V 0.3 FeGa alloy prepared in Example 2 of the present invention;
[0029] Figure 7 Non-local longitudinal resistivity-magnetic field curve and its test schematic diagram of the Mn 1.7 V 0.3 FeGa alloy prepared in Example 2 of the present invention;
[0030] Figure 8 Mn prepared in Example 3 of the present invention 1.6 V 0.4Magnetization intensity - temperature curve of FeGa measured under a magnetic field of 200 Oe;
[0031] Figure 9 For the Mn prepared in Example 3 of the present invention 1.6 V 0.4 Magnetization intensity - magnetic field (M - H) curves of the FeGa alloy obtained by measurement at different temperatures, and (d) is the graph of coercivity and saturation magnetization intensity (3 T) varying with temperature;
[0032] Figure 10 For the Mn prepared in Example 3 of the present invention 1.6 V 0.4 Curve of Hall resistivity of the FeGa alloy varying with magnetic field;
[0033] Figure 11 For the Mn prepared in Example 3 of the present invention 1.6 V 0.4 Carrier concentration n and carrier mobility μ of the FeGa alloy at different temperatures;
[0034] Figure 12 For the Mn prepared in Example 3 of the present invention 1.6 V 0.4 Anomalous Hall conductivity of the FeGa alloy at different temperatures. Detailed implementation manners
[0035] The present invention will be further described in detail below in conjunction with the detailed implementation manners. The given embodiments are only for clarifying the present invention, rather than limiting the scope of the present invention.
[0036] In the following respective embodiments, the inventors respectively measured the isothermal magnetization curve, Hall curve, magnetoresistance curve, EDX energy spectrum and single - crystal X - ray diffraction pattern of the obtained samples to show the relevant characteristics of the materials involved in the present invention. However, for simplicity, only the results of several of the samples are shown, and the corresponding characteristics of other samples have similar results.
[0037] Example 1
[0038] The preparation method of a fully compensated ferrimagnetic material with the composition of Mn 1.8 V 0.2 FeGa in this example is as follows:
[0039] (1) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio Mn:V:Fe:Ga = 1.8:0.2:1:1.
[0040] (2) Since Mn is volatile, an additional 5 at.% of Mn element was weighed.
[0041] (3) Use the arc furnace melting method to prepare Mn 1.8V 0.2 FeGa material: Put the weighed raw materials into the cavity of an arc furnace for melting. During the melting process, the melting time for each side is 4 minutes, and it is turned over three times in total to ensure uniform melting. Place the volatile Mn at the bottom of the crucible of the vacuum arc furnace, and evenly cover other materials on it. Then, introduce high-purity argon gas into the furnace cavity three times repeatedly to ensure that the high-temperature state during the melting process will not oxidize the sample. After the melting is completed and it has completely cooled, take out the sample and weigh it to ensure that the melting loss is less than 1%.
[0042] Put the uniformly melted sample into a quartz tube and seal it under vacuum. Perform heat treatment at 800 - 1100 °C for 150 - 200 hours in a box-type muffle furnace, and then quench it in an ice-water mixture. After quenching, break the quartz tube to take out the sample, and use a cutting machine and a grinding and polishing machine to perform cutting, grinding, and polishing operations respectively to obtain a regular rectangular sample.
[0043] Measure the obtained Mn 1.8 V 0.2 Various physical properties of the FeGa alloy, and collect its various characteristic parameters. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material. The magnetization intensity-temperature curve measured under a magnetic field of 200 Oe is shown in Figure 1 , and it can be seen from the figure that the full compensation temperature is 418 K and the Curie temperature is 438 K. When the temperature approaches the full compensation temperature, the magnetization intensity decreases and reaches zero. The longitudinal resistivity-temperature curve is as shown in Figure 2 , showing that the resistivity decreases with the decrease of temperature, presenting metallicity.
[0044] Example 2
[0045] The preparation method of the fully compensated ferromagnetic material with the composition of Mn 1.7 V 0.3 FeGa in this example is as follows:
[0046] (1) Weigh a total of 5 g of raw materials with a purity of 99.9% according to the atomic ratio of Mn:V:Fe:Ga = 1.7:0.3:1:1. The remaining steps are the same as in Example 1.
[0047] Measure the obtained Mn 1.7 V 0.3 Various physical properties of the FeGa alloy, and collect its various characteristic parameters. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material. The X-ray diffraction spectrum at room temperature is as shown in Figure 3 , and it can be seen from Figure 2 that it is a Heusler alloy with an L21-type crystal structure. The magnetization intensity-temperature curve measured under a magnetic field of 200 Oe is shown in Figure 4, As can be seen from the figure, the full compensation temperature is 200 K and the Curie temperature is 428 K. When the temperature drops to the full compensation temperature, the magnetization decreases and reaches zero. As the magnetic field decreases, the magnetization becomes negative. The curves of the transverse resistivity versus the magnetic field at different temperatures are as Figure 5 shown. From Figure 5 it can be seen that at all temperatures, it exhibits an anomalous Hall effect, and near 130 K, the sign of the anomalous Hall effect changes. The longitudinal resistivity measured on both sides of the sample at 150 K ( Figure 6 a, d) and 300 K ( Figure 6 b, e) is as Figure 6 shown. From Figure 6 a - c, it can be seen that when measured according to the Figure 6 c wiring method, when the magnetic field is positive, the resistivity is small, and when the magnetic field direction is changed to negative, the resistivity is large. This indicates that the magnetization direction caused by the carrier spin is upward, that is, consistent with the positive direction of the magnetic field. When measured on the other side of the sample according to Figure 6 f, the resistivity is large when the magnetic field is positive and small when the magnetic field is negative. That is to say, the magnetization direction caused by the carrier spin is consistent with the negative direction of the magnetic field. And the change of the external magnetic field does not affect the magnetization direction caused by the carrier spin. That is, the carriers are spin-polarized on the same side of the sample, and the spin directions are opposite on both sides of the sample. The non-local longitudinal resistivity - magnetic field curve and its test schematic diagram of the Mn 1.7 V 0.3 FeGa alloy are shown in Figure 7 . It can be seen from the figure that both measurement methods detect the spin polarization phenomenon of the carriers in the alloy, and the spin polarization transport distance can reach 1 cm.
[0048] Example 3
[0049] The preparation method of the fully compensated ferromagnetic material with the composition of Mn 1.6 V 0.4 FeGa in this example is as follows:
[0050] (1) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio of Mn:V:Fe:Ga = 1.6:0.4:1:1. The remaining steps are the same as in Example 1.
[0051] Measure various physical properties of the obtained Mn 1.6 V 0.4 FeGa alloy and collect its various characteristic parameters. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material. The magnetization intensity versus temperature of the Mn 1.6 V 0.4 FeGa alloy measured in the zero-field cooling - field cooling (ZFC - FC) case is as Figure 8As shown, the applied magnetic field during measurement is 200 Oe. It can be seen from the figure that the sample exhibits magnetic compensation behavior, but complete compensation of the magnetic moment does not occur. This is typical P-type ferrimagnetic behavior. The intersection point of the ZFC and FC curves is at 212 K. Mn 1.6 V 0.4 The magnetization intensity versus magnetic field curve (M-H) of the Mn Figure 9 V Figure 9 FeGa alloy is as Figure 9 shown. As the temperature increases, the magnetization intensity shows a gradually decreasing trend and reaches a minimum value (0.026 μB) at 212 K, as can be clearly observed in the b inset of 1.6 V 0.4 Figure 10 and in d of Figure 9 1.6 V 0.4 The curve of the Hall resistivity of the Mn Figure 11 V 1.6 FeGa alloy as a function of magnetic field is as 0.4 Figure 10 shown. It can be seen from the figure that starting from 10 K, the Hall resistivity gradually increases with increasing temperature. It reaches a peak value of 0.48 μΩcm at 150 K. Subsequently, as the temperature further increases, the Hall resistivity gradually decreases and shows an approximately linear trend near 170 K. Then the sign of the Hall resistivity curve reverses. And it reaches a maximum value of 2.36 μΩcm at 300 K. Mn -1 V -1 The carrier concentration n and carrier mobility μ of the Mn -1 V -1 FeGa alloy at different temperatures are as Figure 11 Figure 12
[0052] Example 4
[0053] 1.4 V 0.6 The preparation method of the Mn
[0054] (1) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio Mn:V:Fe:Ga = 1.4:0.6:1:1. The remaining steps are the same as in Example 1.
[0055] Measure the obtained Mn 1.4 V 0.6The various physical properties of the FeGa alloy are measured, and various characteristic parameters thereof are collected. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material.
[0056] Example 5
[0057] In this example, a method for preparing a fully compensated ferromagnetic material with the composition of Mn 1.2 V 0.8 FeGa is as follows:
[0058] (1) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio of Mn:V:Fe:Ga = 1.2:0.8:1:1, and the remaining steps are the same as in Example 1.
[0059] Measure the various physical properties of the obtained Mn 1.2 V 0.8 FeGa alloy, and collect various characteristic parameters thereof. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material.
[0060] Example 6
[0061] In this example, a method for preparing a fully compensated ferromagnetic material with the composition of MnVFeGa is as follows:
[0062] (1) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio of Mn:V:Fe:Ga = 1:1:1:1, and the remaining steps are the same as in Example 1.
[0063] Measure the various physical properties of the obtained MnVFeGa alloy, and collect various characteristic parameters thereof. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material. This material also has spin polarization of longitudinal carriers.
[0064] Example 7
[0065] In this example, a method for preparing a fully compensated ferrimagnetic material with the composition of Mn 1.8 V 0.2 Fe 0.9 Cu 0.1 Ga 0.8 Si 0.2 is as follows:
[0066] (1) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio of Mn:V:Fe:Cu:Ga:Si = 1.8:0.2:0.9:0.1:0.8:0.2, and the remaining steps are the same as in Example 1.
[0067] Measure the obtained Mn 1.8 V 0.2 Fe 0.9 Cu 0.1 Ga0.8 Si 0.2 The various physical properties of the alloy are measured, and various characteristic parameters thereof are collected. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material. This material also has spin polarization of longitudinal carriers.
[0068] Example 8
[0069] In this example, a method for preparing a fully compensated ferrimagnetic material with the composition of Mn 1.8 V 0.2 Cr 0.7 Cu 0.3 Ga 0.9 Ge 0.1 is as follows:
[0070] (2) Weigh 5 g of raw materials with a purity of 99.9% according to the atomic ratio of Mn:V:Fe:Cu:Ga:Si = 1.8:0.2:0.7:0.3:0.9:0.1. The remaining steps are the same as in Example 1.
[0071] Measure the various physical properties of the obtained Mn 1.8 V 0.2 Cr 0.7 Cu 0.3 Ga 0.9 Ge 0.1 alloy, and collect various characteristic parameters thereof. Among them, Table 1 shows the Curie temperature, saturation magnetic moment, etc. of this material. This material also has spin polarization of longitudinal carriers.
[0072] Table 1
[0073]
[0074] As mentioned above, only some specific embodiments of the present invention are described, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A material with complete magnetic compensation effect and high longitudinal spin polarization, characterized in that: Its chemical formula is: Mn 2- a V a Fe 1-b X b Ga 1-c Y c , wherein X is selected from one or more of Cu, Ni, Co, Cr and Ti, Y is selected from one or more of Al, Ge, In, Si, Pb, Sb and Sn, 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0<a+b+c<3; the crystal structure is a face-centered cubic structure, and the space group is F-43m (No.216) or the space group is Fm-3m (No.225).
2. The material according to claim 1, wherein the material is an alloy bulk material; characterized in that , the material has a magnetic full compensation point, at which the material exhibits antiferromagnetism; the full compensation point of the material is adjusted by the type and composition of the doping elements; In the temperature range of 120-400K, the longitudinally transmitted carriers have opposite spin polarization directions on both sides of the alloy bulk material, and the spin polarization transmission distance reaches 1 cm.
3. The method for preparing a material having a complete compensation effect and high longitudinal spin polarization according to claim 1, characterized in that: The following steps are involved: (1) According to the chemical formula Mn 2-a V a Fe 1-b X b Ga 1-c Y c Weighing raw materials, wherein X is selected from one or more of Cu, Ni, Co, Cr and Ti, Y is selected from one or more of Al, Ge, In, Si, Pb, Sb and Sn, 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0<a+b+c<3; (2) The raw materials are made into alloy materials by electric arc furnace smelting.
4. The preparation method according to claim 3, characterized in that: The raw materials described in step (1) are weighed, specifically including using Mn, V, Fe, X, Ga, and Y elements with a purity of not less than 99.9%, weighing them according to the atomic ratio of the alloy, and the total mass is not less than 5 grams.
5. The preparation method according to claim 3, characterized in that: The step (1) further includes the following steps: weighing 5 at.% of the total atomic number of Mn element to balance the melting loss.
6. The preparation method according to claim 3, wherein: The electric arc furnace smelting method comprises the following steps: Place the volatile Mn at the bottom of the crucible of the vacuum arc furnace and evenly cover it with other materials. Then, introduce high-purity argon gas into the furnace chamber three times repeatedly to ensure that the high temperature during the melting process will not oxidize the sample. During the melting process, the melting time for each side is 4 minutes, and the sides are turned back and forth for a total of three times to ensure uniform melting and control the melting loss below 1%; The evenly smelted sample is placed in a quartz tube and sealed in vacuum, heat treated in a box-type muffle furnace at 800-1100°C for 150-200 hours, and then quenched in an ice-water mixture; After quenching, cutting, grinding and polishing are carried out to obtain regular rectangular block materials.
7. Use of the material having a complete magnetic compensation effect and high longitudinal spin polarization according to any one of claims 1 to 2, characterized in that: Used in the preparation of spin electronics devices.
8. The use according to claim 7, characterized in that: The spin electronics devices include magnetic sensors, magnetic random access memories and spin transfer torque.